The Dynamics of Liquidity-adjusted Capital Asset Pricing Model in SubSahara Africa: Evidence from Ghana - Hongxing, Yao; Duduchoge, Solomon (IJRDO - Journal of Applied Management Science, 2017)
This paper estimates the systematic liquidity risk in Ghana using the conditional version of liquidity–adjusted capital asset pricing model in an emerging Ghana’s market. We find that co-movements between stock returns and individual liquidity, market liquidity as well as market returns react differently under different market conditions. Applying the size effect on liquidity, it is evidence that the size effect is stronger for smaller firms in Ghana than for larger firms. While the effect of the recent financial crisis do not exhibit a strong influence on the market, it effect is stronger in the down market than the up market. Finally, we explore the reasons behind the poor performance of stock in Ghana and concluded that lack of transparency and protection for firms are some of the problems.